BioFire FilmArray Meningitis/Encephalitis Panel Utilised for the Unsolved Cases of Meningitis/Encephalitis: A Cross-sectional Study - Bashir Ahmad Fomda; Sanam Rasool Wani; Irfan Ul Haq; Anjum Ara; Gulnaz Bashir; Shugufta Roohi; Sheikh Imtiyaz; Naseer Ahmad Bhat (Journal of Clinical and Diagnostic Research)
Introduction: Syndrome-based diagnosis of various infections is increasingly important. Even in resource-limited countries, adopting a syndrome-based method is essential, as Meningitis/Encephalitis (ME) can be caused by a multitude of agents that require detection through a multiplex assay. Aim: To identify the causative agent in ME cases where at least one conventional microbiological method had failed. Materials and Methods: The present study was a cross-sectional study conducted in the virology section of the Microbiology Department at the Sher-I-Kashmir Institute of Medical Sciences, Srinagar, Jammu and Kashmir, India. The study was carried out from June 2023 to October 2024. A total of 42 cases diagnosed by clinicians as Meningoencephalitis (ME) based on clinical findings (such as fever, headache, neck stiffness and encephalitis, which includes changes in mental status, behaviour and neurological function) were included. The Cerebrospinal fluid (CSF) from these patients had already been submitted to the microbiology lab and had returned negative results on routine CSF culture (Gram stain plus routine bacterial culture) or on routine Polymerase Chain Reaction (PCR) targeting one or two viruses (HSV/Enterovirus/VZV). These samples were subjected to the BioFire FilmArray ME Panel. For statistical analysis, continuous variables such as age and gender were interpreted as means or medians, while categorical variables were interpreted as numbers, percentages, and 95% confidence intervals. A p-value <0.05 was considered significant. Results: Out of the 42 samples tested, organisms were detected in 14 (33.33%) samples, while 28 (66.7%) samples showed no organism. The majority of the identified organisms were viruses (9 or 21.4%), followed by bacteria (4 or 9.52%) and fungi (1 or 2.38%). There were 26 (61.9%) males and 16 (38.1%) females, with ages ranging from one month to 74 years. The most common symptoms among the patients were headache, followed by fever and nausea/vomiting. Conclusion: A syndrome-based diagnosis of ME should be implemented in every institute, following the development of a proper diagnostic algorithm that is both feasible and accurate, based on local experience and available resources.